2020
DOI: 10.1140/epjc/s10052-020-08511-9
|View full text |Cite
|
Sign up to set email alerts
|

Weak cosmic censorship conjecture for the novel 4D charged Einstein–Gauss–Bonnet black hole with test scalar field and particle

Abstract: Recent researches of the novel 4D Einstein–Gauss–Bonnet (EGB) gravity have attracted great attention. In this paper, we investigate the validity of the weak cosmic censorship conjecture for a novel 4D charged EGB black hole with test charged scalar field and test charged particle respectively. For the test charged field scattering process, we find that both extremal and near-extremal black holes cannot be overcharged. For the test charged particle injection, to first order, an extremal black hole cannot be ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 84 publications
(82 reference statements)
1
36
1
Order By: Relevance
“…Interestingly, the solution of the same form has been presented in the conformal anomaly inspired gravity [40,41]. Along this line, the Einstein-Gauss-Bonnet gravity in the 4D spacetime has been explored extensively on various aspects, including the exact solutions [42][43][44][45][46][47][48][49][50][51][52][53][54][55], the quasinormal modes and stability [56][57][58][59][60][61][62][63][64][65][66][67], the observable shadows [68][69][70][71][72][73], the geodesics and gravitational lensing [74][75][76][77][78], and the thermodynamics and cosmic censorship conjecture [79][80][81][82][83][84][85][86].…”
Section: Jhep12(2020)192mentioning
confidence: 99%
“…Interestingly, the solution of the same form has been presented in the conformal anomaly inspired gravity [40,41]. Along this line, the Einstein-Gauss-Bonnet gravity in the 4D spacetime has been explored extensively on various aspects, including the exact solutions [42][43][44][45][46][47][48][49][50][51][52][53][54][55], the quasinormal modes and stability [56][57][58][59][60][61][62][63][64][65][66][67], the observable shadows [68][69][70][71][72][73], the geodesics and gravitational lensing [74][75][76][77][78], and the thermodynamics and cosmic censorship conjecture [79][80][81][82][83][84][85][86].…”
Section: Jhep12(2020)192mentioning
confidence: 99%
“…In past several decades, based on Wald's gedanken experiment, many significant works have been done to check this conjecture. Some of them have indeed proved its validity under certain conditions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], while the others attempt to present its violations [22][23][24][25][26]. Besides, other various possible examples to violate cosmic censorship are also proposed.…”
Section: Introductionmentioning
confidence: 98%
“…Integrating the second-order variation identity on 1 , we have (49) Following the previous calculation steps and the gauge condition of the electromagnetic field such that ζ a δ A a = 0 at H, the Eq. ( 49) can be expressed by…”
Section: The Linear Variational Identitiesmentioning
confidence: 99%
“…After that, many works based on this new experiment [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] show that WCCC is applicable for other kinds of black holes. In addition, more study on the test for WCCC can be found in [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%